(untitled) (Global Journal of Science Frontier Research, 2022)
White light interferometry was applied to obtain the rate change of an oxide film growth of aluminum samples during the anodization in aqueous solutions The thickness d of the oxide film was determined by Fabry-Perot i e white light interferometry In other words for the first time an electromagnetic i e Fabry-Perot method was utilized to obtain the rate change of the oxide film growth of aluminum samples rather than the electronic i e direct current DC or alternating current AC methods as a function of the time t of the anodization processes Therefore the abrupt rate change of the d d dt was called anodization-emission spectroscopy The anodization process of the aluminum samples was carried out by the DC method in different sulphuric acid concentrations 0 0 2 4 6 8 10 H2SO4 at room temperature In the meantime the Fabry-Perot interferometry was used to determine the difference between d of two subsequent values d d as a function of the elapsed time dt of the DC experiment for the aluminum samples in H2SO4 solutions The Fabry-Perot interferometry was based on a fiber-optic sensor to make real time-white light interferometry possible at the aluminum surfaces in the acid solutions Also an abrupt rate change of the d d dt of the oxide film of the aluminum in 2 0 4 0 6 0 8 8 10 0 H2SO4 and in deionized water 0 0 H2SO4 was observed to occur once between 10 to 20 minutes Then the d d dt of the oxide film was recorded around zero between 20 to 30 minutes Eventually the d d dt of the oxide film was gradually increased during the remaining elapsed time of the experiment